Assessment of Physical Child Abuse Risk in Parents with Children Referred to Child and Adolescent Psychiatry. (4th July 2017) - Van Looveren, Natalie; Glazemakers, Inge; Van Grootel, Linda; Fransen, Erik; Van West, Dirk
Abstract : Given the vulnerability of the child psychiatric population, this study examined whether parenting a child referred to a child and adolescent psychiatry department leads to a higher risk of physical child abuse and if that risk is associated with a specific child psychopathology. The clinical sample consisted of caregivers with a six‐to‐11‐year‐old child who consulted child and adolescent psychiatry for a psychiatric assessment. The Dutch Child Abuse Potential Inventory (CAPI), socio‐demographic data and child psychiatric diagnosis were collected from 59 caregivers of 59 children. Ten per cent of the sample obtained an Abuse scale score indicative of a potential risk for physically maltreating their child. Compared to a non‐clinical sample, this study showed a two and a half times higher risk potential for physical child abuse in caregivers with children referred to child and adolescent psychiatry. The elevated risk was not associated with a specific child psychiatric diagnosis. The caregivers at risk were more unhappy and experienced more problems with their child, their family and with others. Results support the need for implementing a standard risk assessment for physical child abuse in a child psychiatric setting. Copyright © 2017 John Wiley & Sons, Ltd. 'This study examined whether parenting a child referred to a child and adolescent psychiatry department leads to a higher risk of physical child abuse' Key Practitioner Messages: Compared to a non‐clinical sample, there is a two and a half times higher risk potential for physical child abuse in caregivers with children with mental health problems examined with the self‐report screening questionnaire CAPI. Child psychopathology in general is associated with an elevated potential for physical child abuse; there is no correlation with a specific child psychiatric disorder. There is a need for implementing a standard risk assessment for child abuse in a clinical child psychiatric setting.